2011
DOI: 10.9735/0975-2862.3.2.50-61
|View full text |Cite
|
Sign up to set email alerts
|

Evolution Without Genes

Abstract: Abstract-Nowadays genes are claimed to explain almost everything that is somehow or another connected with manifestations of the biological life on the Earth, including evolution. It is now clear, however, that major incongruities exist and that there is only a weak relationship between biological complexity and the number of protein coding genes. The genome can be divided into two main sections, the coding (genes) and non coding portions. Non coding DNAs have been considered as non-functional DNA by many auth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 58 publications
1
2
0
Order By: Relevance
“…However, the differences between them are detected when the number of Q-HRs expressed as a percentage from the number of chromosomes analyzed (176.1%, 172.5% and 218.7%) of Kazakh, Russian and Uighur people, respectively. In other words, the increase in the mean number of Q-HRs are accompanied by increases in absolute Q-HR frequencies on all the autosomes, and vice versa, that matched with all of our previous observations [4][5][6][7][8][9][10][11]17]. *Q-HRs frequency from the number of chromosomes analyzed; **Q-HRs frequency as percentage of the overall number of chromosomal Q-HR.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…However, the differences between them are detected when the number of Q-HRs expressed as a percentage from the number of chromosomes analyzed (176.1%, 172.5% and 218.7%) of Kazakh, Russian and Uighur people, respectively. In other words, the increase in the mean number of Q-HRs are accompanied by increases in absolute Q-HR frequencies on all the autosomes, and vice versa, that matched with all of our previous observations [4][5][6][7][8][9][10][11]17]. *Q-HRs frequency from the number of chromosomes analyzed; **Q-HRs frequency as percentage of the overall number of chromosomal Q-HR.…”
Section: Resultssupporting
confidence: 88%
“…We suppose, that our new data on the populations living in southern Kazakhstan does not contradict hypothesis of a possible selective value of chromosomal Q-HRs in human adaptation to different climatic and geographical conditions of the Earth. Previously, we have repeatedly shown that the amount of Q-chromosomal HRs in the genome of human populations depends largely on the peculiarity of climatic and geographical conditions of their place of residence, and not on their racial and ethnic features [4][5][6][7][8][9][10][11][12]16]. The lack of statistically significant differences in quantitative content of chromosomal Q-HRs between the two Kazakh samples from the southern Kazakhstan should not be surprising.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation